Deteksi Mikrometastasis pada Bulky Kelenjar Getah Bening Karsinoma Serviks Stadium IA-IIB Menggunakan Sitokeratin AE1/AE3 - Angeline, Reni; Tjahjadi, Hartono; Wuyung, Puspita Eka (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2020)
BackgroundCervical uterine carcinoma is a primary malignant disease of the uterine cervix. The presence or absence of metastasis in lymphnodes does not alter the stage but affects recurrence, survival, and therapy. Immunohistochemistry stains of the AE1/AE3cytokeratin can assist in the diagnosis and determine the small focus of carcinoma metastasis. In this study, we analyzedimmunohistochemistry cytokeratin AE1/AE3 could determine micrometastasis in bulky lymph nodes negative.MethodsThis study used cross-sectional design. The sample consisted of 52 cases of stage IA-IIB cervical carcinoma performed by radicalhysterectomy and lymphadenectomy accompanied by negative bulky lymph nodes at the Department of Anatomical PathologyFaculty of Medicine University of Indonesia/Cipto Mangunkusumo Hospital (FKUI/RSCM) from January 2011 to June 2017. Allcases stained by immunohistochemistry cytokeratin AE1/AE3.ResultsBulky Lymph Nodes Cervical Carcinoma stage IA-IIB, histopathologic diagnose of non keratinized squamous cell carcinoma,moderate differentiation degree, no lymphovascular invasion and deepest invasion >5.0 mm. Immunohistochemistry staining ofAE1/AE3 cytokeratin showed no micrometastasis in all cases.ConclusionThe immunohistochemistry staining of AE1/AE3 cytokeratin used in Bulky Lymph Nodes Cervical Carcinoma stage IA-IIB could notdetected micrometastasis in all cases.